2022
DOI: 10.1136/rmdopen-2022-002454
|View full text |Cite
|
Sign up to set email alerts
|

How do multiple long-term conditions impact on the cost-of-illness in early rheumatoid arthritis?

Abstract: ObjectiveMultiple long-term conditions (MLTCs) are prevalent in rheumatoid arthritis (RA) and associated with worse outcomes and greater economic burden. However, little is known about the impact of MLTCs on the cost-of-illness (COI) in early RA, including direct and indirect costs. The objective of this study was to quantify this impact on COI.MethodsThe Scottish Early Rheumatoid Arthritis study is a national cohort of adults with new-onset RA. Direct costs were estimated applying relevant unit costs to healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The estimated mean disease duration in our study is high, and studies have found that greater treatment costs are related to longer disease duration 25 26 . Other studies conducted globally have reported average annual treatment costs for RA patients, with a 2001 study in the United States estimating $9519 27 and a Scottish study estimating £4444 28 . Similarly, the average annual total cost for patients with high disease activity was $13,303 more than for patients in remission 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The estimated mean disease duration in our study is high, and studies have found that greater treatment costs are related to longer disease duration 25 26 . Other studies conducted globally have reported average annual treatment costs for RA patients, with a 2001 study in the United States estimating $9519 27 and a Scottish study estimating £4444 28 . Similarly, the average annual total cost for patients with high disease activity was $13,303 more than for patients in remission 25 .…”
Section: Discussionmentioning
confidence: 99%